Recent Progresses in Electrocatalysts for Water Electrolysis - Khan, Muhammad Arif; Zhao, Hongbin; Zou, Wenwen; Chen, Zhe; Cao, Wenjuan; Fang, Jianhui; Xu, Jiaqiang; Zhang, Lei; Zhang, Jiujun (Electrochemical energy reviews, 2018)
The study of hydrogen evolution reaction and oxygen evolution reaction electrocatalysts for water electrolysis is a developing field in which noble metal-based materials are commonly used. However, the associated high cost and low abundance of noble metals limit their practical application. Non-noble metal catalysts, aside from being inexpensive, highly abundant and environmental friendly, can possess high electrical conductivity, good structural tunability and comparable electrocatalytic performances to state-of-the-art noble metals, particularly in alkaline media, making them desirable candidates to reduce or replace noble metals as promising electrocatalysts for water electrolysis. This article will review and provide an overview of the fundamental knowledge related to water electrolysis with a focus on the development and progress of non-noble metal-based electrocatalysts in alkaline, polymer exchange membrane and solid oxide electrolysis. A critical analysis of the various catalysts currently available is also provided with discussions on current challenges and future perspectives. In addition, to facilitate future research and development, several possible research directions to overcome these challenges are provided in this article. Graphical Abstract